The Effects of Covid-19 on the Financial Sector and the Role of Social Media as an Advertising Tool in these Trying Times in Zimbabwe - Chirume, Enesiti (Journal of Economics and Behavioral Studies, 2021)
This study identifies the effects of COVID-19 on the financial sector and explores the part played by social media as an advertising instrument in Zimbabwe. The objectives of the study are - (i) to identify the effects of COVID-19 on the financial sector in Zimbabwe. ii) To appraise the function of social media as an advertising vehicle in these trying times, in Zimbabwe. Drawing respondents from ten (10) leading financial institutions in Zimbabwe, the study uses a self-administered interview schedule and adopts the qualitative research design. Challenges identified range from managing the legal tender and interchangeability to methodizing working routine (dropping profits and staff well-being). There are also pressures on financial institutions notably, the rise of fintech within the sector to serve customer needs. Even though the pandemic has a terrible negative impact, thanks to social media for becoming primary sources of information. This paper agrees with some scholarly views on what ought to be the additional and new role of social media as an advertising tool- and that is relating social media benefactions to the concurrent milieu. For financial institutions, it is not business as usual. The substance of the matter is that duration of the plight and its impact are still undetermined in Zimbabwe and elsewhere. This phase presents a singular chance for the financial institutions in Zimbabwe to use social media advertising to its best, to tether with clients in significant ways. This includes adjusting advertising campaigns, evaluating the language used in advertisements and becoming aware of consumers’ increased anxiety during these trying times. The study recommends that financial institutions have to think through creative advertising strategies and practices that may navigate the business through this “new normal.” They should use social media more for communal rather than for commercial purposes now and after.